Formule e itinerari del ‘debut-et-la fin’ nella Contemplazione della morte - Fabris, Angela (Archivio d’Annunzio, 2021)
The essay proposes a selective reading of the beginnings and the endings of the four prose texts of Contemplazione della morte (1912), in their connections, according to the different typologies and functions. Attention is given to the two dedicatees, Pascoli and Bermond, together with natural landscapes and atmospheric notations, as well as to the importance given to silence and to the vitalistic image of the “cagna”, which in the finale imposes itself on that of the drowned man.